Profiling the segments of visitors to Portuguese protected areas - Marques, C. (2010)
This study identifies the diversity of domestic visitors to Portuguese protected areas (PPA) based on benefit segmentation. The segments of PPA visitors are also compared with other nature-based tourist segments using some empirical benefit segmentation literature. Data were collected by means of a self-administered questionnaire and multivariate statistics techniques (principal components, hierarchical and K-means cluster analyses) were applied. Five distinct segments of visitors were identified based on the motivation for their visit and further characterized by the perceived importance of activities, facilities and services, frequency of visit and socio-demographics. Three segments are nature-focused and two are focused on activities or events. Only one segment shows specific interests and motivations associated with ecotourism and similar characteristics to international ecotourists; moreover, the reasons for the visit in one segment are unrelated to any of the motivations of nature-based tourism. Some implications for management are also described.